Relación entre el estrés académico y las estrategias de afrontamiento en estudiantes universitarios - Aservi Rodrigo, Micaela Veronica (2022)
The pandemic produced by (COVID-19) has had effects on many people worldwide. An established measure to prevent the spread of the coronavirus was to migrate from classical education to online education. This has produced unfavorable effects on university students, both in their learning process and in their mental wellness. To face the demands of the pandemic and social distancing, as well as the new forms of teaching learning, students require certain coping strategies that enable them to adapt satisfactorily to it. For this reason, the purpose was to analyze the relationship between academic stress and the coping strategies used by students, during the pandemic. 10 articles were selected, following the PRISMA 2020 criteria. For this, databases were consulted, such as Scopus, Web of Science, Ebsco, Science Direct, and APA PsycNet. It was found that academic stress and coping strategies show a statistically significant negative relationship. The strategies most used by students to deal with this context are humor, acceptance, active coping, religion, and planning. While the strategies used less are denial relief and use of substances